Study of the Performance of a Thermoelectric Refrigeration Membrane Cold Chamber Distillation Component - Hu, Junhu; Wu, Shunli; Liu, Hao; Yang, Xiaohong (Frontiers in Energy Research, 2022)
Thermoelectric Refrigeration Membrane Distillation (TERMD) is an emerging membrane-based evaporation technology with excellent prospects for separation industries. However, the development of the TERMD system was further limited by excellent membrane component properties. In this paper, a cold chamber component of a TERMD is manufactured. Then, the cooling performance of the component is studied to examine the coupling between the Thermoelectric Refrigeration (TER) and the Membrane Distillation (MD) process. Moreover, the effects of the membrane components properties are studied by changing the water flow rate, and the input current of thermoelectric refrigeration. The results showed that when the TERMD cold room inlet current is maintained stable and the heat dissipation intensity increases, the cooling temperature gradually decreases. Also, the temperature on the cold side tends to stabilize while the flow rate exceeds 600 L/h. In addition, the input power decreases as the heat dissipation intensity increases in the cooling dissipation intensity of the Thermoelectric Refrigeration Component (TERC) cold chamber is kept stable. And, the input power will reach a critical value while the water volume flow rate is over 500 L/h. Furthermore, the cooling rate reaches the maximum of 1.59 at the water volume flow rate of 700 L/h while the operating current of the TERC is 12 A. It is concluded that the thermoelectric refrigeration component can supply great refrigeration power and a high Coefficient of Performance (COP) under small current conditions for the analysis of the thermoelectric performance of the TERC.